Influence of magnetic well on electromagnetic turbulence in the TJ-II stellarator. (29th July 2016) - Castejón, F; de Aguilera, M; Ascasíbar, E; Estrada, T; Hidalgo, C; López-Fraguas, A; Ochando, M A; Yamamoto, S; Melnikov, A V; Eliseev, L G; Krupnik, L I
Abstract: A magnetic well scan has been performed in the TJ-II stellarator to investigate the confinement properties with different values of the well, or even of the hill, and to explore the properties of electromagnetic turbulence. Stable plasmas have been obtained in theoretically Mercier-unstable configurations, and the electrostatic turbulence levels in the edge are increased. Three families of modes appear during the experiments: (1) a family of modes of Alfvénic nature with high frequencies; (2) a second set of modes of middle frequencies (tens of kHz) and (3) an oscillation at f ≈ 10–20 kHz happens in several cases. In spite of the fact that the vacuum rotational transform is very similar in all of the cases, the Alfvénic mode family changes drastically when decreasing the magnetic well, showing a non-monotonic behaviour of the amplitude, and a decrease of the typical frequencies. This behaviour cannot be explained only by current or density variations, so the effect of the modification of the configuration is playing a key role. Regarding the intermediate frequencies, a coherent mode appears with decreasing frequency as the magnetic well decreases. This mode is a candidate for a GAM, which can survive in these TJ-II plasmas, despite of the strong damping these modes should suffer in this device.